142 Surgical Treatment of Chronic Femoral and Tibial Osteomyelitis: A Scoping Review. (12th October 2021) - Lau, E; Arshad, Z; Aslam, A; Thahir, A; Krkovic, M
Abstract: Aim: The management of osteomyelitis, an inflammatory process of the bone that causes destruction and necrosis, is complex, and many authors report different techniques. This scoping review aims to identify and summarise literature on the management of chronic femoral and tibial osteomyelitis to further the reader's understanding of potential management strategies and thereby explore areas for further research. Method: The Joanna Briggs Institute methodological framework was used. PubMed, EMBASE, MEDLINE, Emcare and CINAHL searches were conducted for articles reporting the management of chronic osteomyelitis of the femur and tibia. Two reviewers independently screened the title/abstract and full text against the pre-defined criteria. Results: Altogether, 1223 articles were identified and 52 were finally included. Various management strategies were reported, and the main principles shared across these strategies included antibiotic therapy, removal of infected tissue and management of dead-space. 75.45% of patients presented with stage III or IV disease, using the Cierny-Mader classification. The most commonly isolated organism was Staphylococcus aureus . The proportion of patients who achieved remission without recurrences during follow-up period ranged between 59.3% - 100.0%. Conclusions: Excellent outcomes, in terms of remission and lack of recurrence, were reported in the majority of studies. It is clear that specific patient and treatment-related factors may affect outcomes but further high-level research such as randomized control trials are required to investigate this further.